Robot-assisted radical prostatectomy: Advancements in surgical technique and perioperative care - Palma-Zamora, Isaac; Abdollah, Firas; Rogers, Craig; Jeong, Wooju (Frontiers in Surgery, 2022)
We reviewed the evolving strategies, practice patterns, and recent advancements aimed at improving the perioperative and surgical outcomes in patients undergoing robotic-assisted radical prostatectomy for the management of localized prostate cancer.